High-transparency invisible car cover self-cleaning film as well as preparation method and application thereof
Through the combination of modified nano alumina and functional additives, the shortcomings of the self-cleaning film of high-transparent invisible car clothing in waterproof, antistatic, aging resistance and mechanical and mechanical properties are solved, and better comprehensive performance and long service life are achieved. , meets the diversity needs of the transportation field.
Patent Information
- Application Number
- CN202411296937.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-20
AI Technical Summary
The existing high-transparent invisible car clothing self-cleaning membranes have unbalanced performance or lack in waterproof, anti-static, aging resistance and mechanical and mechanical properties, which cannot meet the needs of diverse performance in the field of transportation.
Compound nanoalumina particles are prepared by ultrasonic dispersion and hot pressing using modified nanoalumina, nanosilicon dioxide and nanozirconia compositions, as well as functional additives such as epoxy block polyether and polyethylene glycol methyl ether. , a frame structure is formed to improve the mechanical and waterproof properties of the film layer, and the molecular network construction of the film layer is enhanced by functional additives to achieve uniform dispersion and stability of the film layer.
While maintaining excellent self-cleaning performance, it significantly improves the waterproof, aging resistance and anti-static properties of the film, extends its service life, meets the diverse performance needs of the transportation vehicle field, and shows excellent protection in daily life Effect.
Smart Images

Figure BDA0005046319070000181 
Figure BDA0005046319070000191
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane materials, and in particular to a highly transparent invisible car cover self-cleaning membrane and a preparation method and application thereof. Background Art
[0002] At present, the cleaning of automobile bodies, train bodies, automobile glass, train windows, and insulation films is achieved by water washing, which cannot achieve self-cleaning treatment, nor can it achieve transparent protection and new use effects. However, with the development of science and technology and the higher requirements of transportation for product performance, the emerging technology direction of high-transparency invisible car cover self-cleaning film has gradually come into people's view.
[0003] High-transparency invisible car cover self-cleaning film is a high-performance car protective film, usually made of high-quality resin materials. Its main function is to provide an additional layer of protection without affecting the appearance of the vehicle to prevent the paint from being scratched by small stones, branches and other road debris, as well as damage from ultraviolet rays, acid rain and other environmental factors. The self-cleaning property means that this film has a certain ability to reduce the adhesion of dirt, dust and other pollutants, or make these pollutants easier to wash off, which is usually due to special treatment or coating on the surface of the film. But at the same time, the existing high-transparency invisible car cover self-cleaning film still has uneven performance or lack of performance in terms of new properties such as waterproof, antistatic, aging resistance, corrosion resistance and mechanical mechanical properties.
[0004] Therefore, in order to solve the above problems, the present application provides a high-transparency invisible car cover self-cleaning film and a preparation method thereof. The high-transparency invisible car cover self-cleaning film prepared in the present application can maintain excellent self-cleaning performance and mechanical properties while maintaining good waterproof, aging resistance, corrosion resistance and anti-static properties, meeting the diverse performance requirements of invisible car cover films in the existing transportation field, achieving good comprehensive performance and long service life, and has very excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a highly transparent invisible car cover self-cleaning film. The raw materials, calculated by mass, are: 20 to 40 parts of base emulsion, 30 to 60 parts of nanoparticles, 10 to 20 parts of functional additives, 20 to 30 parts of diluents, 15 to 25 parts of silicone oil, 1 to 3 parts of leveling agents, 2 to 5 parts of wetting agents, and 1 to 3 parts of dispersants.
[0006] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (30-38): (35-45): (12-18).
[0007] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (33-36): (38-42): (14-16).
[0008] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (30-38): (22-26): (18-24).
[0009] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (33-36): (24-25): (20-22).
[0010] As a preferred solution, the base emulsion is a composition of modified acrylic emulsion and fluorocarbon emulsion.
[0011] As a preferred solution, the mass ratio of the modified acrylic emulsion to the fluorocarbon emulsion is (2-3): (0.8-1.2).
[0012] As a preferred solution, the mass ratio of the modified acrylic emulsion to the fluorocarbon emulsion is (2.2-2.5): (0.8-1).
[0013] As a preferred solution, the modified acrylic emulsion is an organosiloxane-modified acrylic emulsion.
[0014] As a preferred solution, the viscosity of the modified acrylic emulsion is 150-300 mPa·s at 25°C.
[0015] As a preferred solution, the solid content of the modified acrylic emulsion is 50-55 wt %.
[0016] As a preferred solution, the fluorine content of the fluorocarbon emulsion is 10-15wt%.
[0017] As a preferred solution, the solid content of the fluorocarbon emulsion is 40-48wt%.
[0018] As a preferred solution, the nanoparticles are a composition of modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide.
[0019] As a preferred solution, the mass ratio of the modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide is (2-2.5): (1-1.4): (1-1.4).
[0020] As a preferred solution, the mass ratio of the modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide is (2.2-2.4): (1.3-1.4): (1.1-1.2).
[0021] As a preferred solution, the average particle size of the nano-silicon dioxide is 40 to 60 nm.
[0022] As a preferred solution, the average particle size of the nano zirconium oxide is 10 to 20 nm.
[0023] As a preferred solution, the preparation method of the modified nano-alumina comprises the following steps: S1: adding the nano-alumina to a mixed solvent of ethanol and deionized water, uniformly dispersing it by ultrasonication at 200-250W, adjusting the pH value to 9-10 by triethanolamine, then adding tetraethyl orthosilicate, isopropanol and silane coupling agent, heating to 65-70°C and keeping the temperature for reaction for 2.5-3h, after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying it to obtain pretreated nano-alumina; S2: adding the pretreated nano-alumina to deionized water, adding sodium dodecylbenzene sulfonate, succinic anhydride and hydrofluoric acid, keep warm at 60-80°C for 1.5-2h, add aluminum nitrate trihydrate, mix terephthalic acid and isophthalic acid, stir evenly, and transfer to a sealed reaction container; S3: control the pressure of the sealed reaction container to 2-2.1MPa, heat the reaction at 195-200°C for 10-12h, and after the reaction is completed, naturally cool to 60-65°C to obtain a mixed solution, then add zinc nitrate and dimethylimidazole to every 100 parts of the mixed solution, mix and stir, keep warm for 1.5-2h, after completion, centrifuge and filter the product, wash with ethanol for 2-3 times, and then vacuum dry to obtain.
[0024] As a preferred solution, the mass ratio of the nano-alumina, tetraethyl orthosilicate, isopropyl alcohol and silane coupling agent is (3.5-3.8): (0.8-0.9): (0.2-0.25): (0.08-0.12).
[0025] As a preferred solution, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0026] As a preferred solution, in the mixed solvent of ethanol and deionized water, the mass ratio of ethanol to deionized water is (1-1.5):(4-4.5).
[0027] As a preferred solution, the mass ratio of the pretreated nano-alumina, sodium dodecylbenzene sulfonate, succinic anhydride and hydrofluoric acid is (4-4.5): (0.3-0.4): (1.5-1.8): (10-12).
[0028] As a preferred solution, the mass ratio of the pretreated nano-alumina, aluminum nitrate trihydrate, terephthalic acid and isophthalic acid is (4-4.5): (3-3.5): (1.5-2): (0.6-1).
[0029] As a preferred solution, the mass ratio of zinc nitrate to dimethylimidazole in the mixed solution is 100:(3-4):(1.6-1.8).
[0030] As a preferred solution, the average particle size of the nano-alumina is 15 to 25 nm.
[0031] As a preferred solution, the average particle size of the modified nano-alumina is 640-780 nm.
[0032] The modified nano-alumina, nano-silicon dioxide and nano-zirconia combination scheme added in this application can effectively improve the mechanical properties, aging corrosion resistance and waterproof and moisture-proof properties of the self-cleaning film, thereby maintaining good film cleanliness. The modified nano-alumina particles can form composite particles with framework particles as the internal body and nano-alumina as the outer layer through the bonding action of coordination bonds, so that the particles can enhance their connection force with the molecules of the film system through the active modification of the surface groups, thereby achieving uniform dispersion in the film layer and particle stability after solidification, avoiding segregation and agglomeration. On the other hand, the formed composite structure can guide the contact between the water molecules inside the film layer and the framework particles through the guiding effect of the surface alumina particles on the water molecules, thereby achieving stable adsorption of the internal water, and maintaining the desorption state at a common ambient temperature (generally 65°C), clearing the water inside the film layer, greatly reducing the penetration rate of water molecules and increasing the penetration resistance of active molecules and free groups with water molecules as carriers, thereby obtaining good waterproof and aging corrosion resistance.
[0033] In addition, the modified composite nano-alumina particle structure can play a good supporting role when the film layer is subjected to external force based on the skeleton structure of the framework particles, and because of the connection between the surface alumina and the organic molecules of the film layer, it plays a certain tensile connection role, maintaining good mechanical properties of the film layer; and on the surface of the film layer, the extremely low surface energy of the composite particle structure can promote the formation of a smoother and high fluorocarbon resin film layer surface, and the smoother film layer surface greatly reduces the retention time of surface water molecules on the film layer surface, and thus the aggregation of water molecules cannot be formed in a short period of time, and thus an effective hydration layer surface cannot be formed. In most application environments, water molecules will be removed by gravity due to the smooth effect and hydrophobic properties of the surface, thereby obtaining excellent film self-cleaning, waterproof and aging corrosion resistance and other properties.
[0034] As a preferred solution, the functional auxiliary agent is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether.
[0035] As a preferred solution, the mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).
[0036] As a preferred solution, the mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4.2-4.5): (3.2-3.3): (1.2-1.5).
[0037] As a preferred solution, the weight average molecular weight of the polyethylene glycol methyl ether is 400 to 800 Da.
[0038] As a preferred solution, the weight average molecular weight of the epoxy block polyether is 6000-8000 Da.
[0039] As a preferred solution, the ethylene oxide block content of the epoxy block polyether is 60 to 70 wt%.
[0040] As a preferred solution, the aromatic phenol polyoxyethylene ether is a combination of phenethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether.
[0041] As a preferred solution, the mass ratio of the phenethylphenol polyoxyethylene ether to the trimethylstyrenephenol polyoxyethylene ether is (3-4): (0.6-0.8).
[0042] As a preferred solution, the HLB value of the phenethylphenol polyoxyethylene ether is 10-12.
[0043] As a preferred solution, the HLB value of the trimethylstyrene phenol polyoxyethylene ether is 15-18.
[0044] The above-mentioned composite functional additives added in the present application can effectively assist in improving the mechanical properties of the film layer, and can effectively ensure the waterproof and aging corrosion resistance of the self-cleaning film. The epoxy block polyether and polyethylene glycol methyl ether added in the present application can enhance the molecular network construction assistance effect of the overall functional additives in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths are easy to form entanglements with each other, which helps to improve the intermolecular force, and then assist in improving the mechanical properties of the film layer, and the addition of arylphenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so as to better use epoxy block polyether and polyethylene glycol methyl ether as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing friction mechanical properties. On the other hand, the compounded functional additives can also assist the formation of a smooth film surface of the fluorocarbon resin on the surface, thereby improving the overall waterproof and aging corrosion resistance of the film layer.
[0045] As a preferred solution, the diluent is at least one of ethanol, methanol, isopropanol or ethyl acetate.
[0046] As a preferred solution, the diluent is ethanol or isopropanol.
[0047] As a preferred solution, the leveling agent is at least one of organic silicon leveling agents.
[0048] As a preferred solution, the leveling agent is an organic silicon leveling agent BYK-306.
[0049] As a preferred solution, the wetting agent is at least one of non-ionic wetting agents.
[0050] As a preferred solution, the dispersant is at least one of polyurethane, acrylic and betaine.
[0051] As a preferred solution, the dispersant is polyurethane or acrylic.
[0052] As a preferred solution, the dispersant is acrylic BYK-163.
[0053] The second aspect of the present application provides a method for preparing the above-mentioned high-transparency invisible car cover self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil, and basic emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours to obtain the product.
[0054] The second aspect of the present application provides an application of the above-mentioned high-transparency invisible car cover self-cleaning film in the field of protective films for car bodies, train bodies, car windows and train windows.
[0055] The beneficial effects of this application are:
[0056] 1. The highly transparent invisible car cover self-cleaning film provided in the present application can maintain excellent self-cleaning performance and mechanical properties while maintaining good waterproof, aging resistance, corrosion resistance and anti-static properties. It not only meets the diverse performance requirements of the existing transportation field for invisible car cover films, but also plays an excellent protective role in people’s daily lives, especially in scenes such as waterproof and self-cleaning of house bathroom tiles, kitchen tiles, partition glass, door and window glass, and mirrors, achieving good comprehensive performance and long service life, and has very excellent application prospects.
[0057] 2. A highly transparent invisible car cover self-cleaning film provided in the present application, the added modified nano-alumina can enhance its connection force with the molecules of the film system through the active modification of the surface groups, thereby achieving uniform dispersion in the film and stability of the particles after solidification, avoiding segregation and agglomeration. On the other hand, the formed composite structure can guide the contact between the water molecules inside the film and the framework particles through the guiding effect of the surface alumina particles on the water molecules, thereby achieving stable adsorption of internal moisture, clearing the moisture inside the film, greatly reducing the penetration rate of water molecules and increasing the penetration resistance of active molecules and free groups with water molecules as carriers, thereby obtaining good waterproof and aging and corrosion resistance.
[0058] 3. A highly transparent invisible car cover self-cleaning film provided in the present application, the added modified composite nano-alumina particle structure can play a good supporting role when the film layer is subjected to external force based on the skeleton structure of the framework particles, and because of the connection between the surface alumina and the organic molecules of the film layer, it plays a certain tensile connection role, thereby maintaining good mechanical properties of the film layer; and on the surface of the film layer, the extremely low surface energy of the composite particle structure can promote the formation of a smoother and high fluorocarbon resin film layer surface, and the smoother film layer surface greatly reduces the retention time of surface water molecules on the film layer surface, and thus water molecules cannot form aggregation in a short period of time, and thus an effective hydration layer surface cannot be formed. In most application environments, water molecules will be removed by gravity due to the smoothing effect and hydrophobic properties of the surface, thereby obtaining excellent film self-cleaning, waterproofing and aging and corrosion resistance and other properties.
[0059] 4. The highly transparent invisible car cover self-cleaning film provided in the present application, the added compound functional additives can effectively help improve the mechanical properties of the film layer, and can effectively ensure the waterproof and aging corrosion resistance of the self-cleaning film. Epoxy block polyether and polyethylene glycol methyl ether can enhance the molecular network construction assistance effect of the overall functional additives in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths can easily form entanglements with each other, which helps to improve the intermolecular force, thereby helping to improve the mechanical properties of the film layer, and the addition of aromatic phenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so that the epoxy block polyether and polyethylene glycol methyl ether can be better used as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing the friction mechanical properties. DETAILED DESCRIPTION
[0060] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0061] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0062] Example 1
[0063] Example 1 The first aspect provides a highly transparent invisible car cover self-cleaning film. The raw materials, in parts by mass, are: 34.6 parts of base emulsion, 39.5 parts of nanoparticles, 15.5 parts of functional additives, 24.8 parts of diluents, 21 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.
[0064] The base emulsion is a composition of modified acrylic emulsion and fluorocarbon emulsion, and the mass ratio of the two is 2.4:1.
[0065] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion with a viscosity of 240 mPa·s, a temperature of 25° C., and a solid content of 52.2 wt %. The product is a SH-1046 model product purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0066] The fluorocarbon emulsion has a fluorine content of 11.6 wt % and a solid content of 46.5 wt %, and is purchased from Jining Tangyi Chemical Co., Ltd. under the model CF-801.
[0067] The nanoparticles are a composition of modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide, and the mass ratio of the three is 2.4:1.4:1.1.
[0068] The average particle size of nano-silicon dioxide is 55nm, and the average particle size of nano-zirconia is 14nm.
[0069] The preparation method of modified nano-alumina comprises the following steps, calculated by mass: S1: adding 3.6 parts of nano-alumina to a mixed solvent of ethanol and deionized water (a total of 180 parts of the mixed solvent, and a mass ratio of ethanol to deionized water of 1:4), uniformly dispersing by 220W ultrasonic dispersion, adjusting the pH to 9.8 with triethanolamine, then adding 0.82 parts of tetraethyl orthosilicate, 0.22 parts of isopropanol and 0.1 parts of silane coupling agent, heating to 68°C and keeping the temperature for reaction for 3 hours, after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated nano-alumina; S2: adding 4.2 parts of pretreated nano-alumina to 200 parts of deionized water, adding 0.3 8 parts of sodium dodecylbenzene sulfonate, 1.68 parts of succinic anhydride and 11.5 parts of hydrofluoric acid are kept at 65°C for 2h, and then 3.1 parts of aluminum nitrate trihydrate, 1.65 parts of terephthalic acid and 0.75 parts of isophthalic acid are added, mixed and stirred evenly, and transferred to a sealed reaction container; S3: Control the pressure of the sealed reaction container to 2.1MPa, heat the reaction at 200°C for 11.5h, and after the reaction is completed, naturally cool to 60°C to obtain a mixed solution, and then add 3.2 parts of zinc nitrate and 1.8 parts of dimethylimidazole to every 100 parts of the mixed solution, mix and stir, and keep warm for 2h. After completion, centrifuge and filter the product, wash it with ethanol for 3 times, and then vacuum dry it to obtain.
[0070] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0071] The average particle size of the modified nano-alumina is 691nm.
[0072] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.
[0073] The weight average molecular weight of polyethylene glycol methyl ether is 400 Da, and the product of the corresponding molecular weight model is purchased from Haian Petrochemical Company in Jiangsu Province.
[0074] The weight average molecular weight of the epoxy block polyether is 7800 Da, the ethylene oxide block content is 70 wt %, and the product is an ethylene oxide-propylene oxide block copolyether product of model L87 purchased from BASF.
[0075] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.
[0076] The HLB value of phenylethylphenol polyoxyethylene ether is 11, and it was purchased from the corresponding HLB value product sold by Nanjing Kexing Chemical Co., Ltd.; the HLB value of trimethylstyrenephenol polyoxyethylene ether is 16, and it was purchased from the corresponding HLB value product sold by Jiangsu Hai'an Petrochemical.
[0077] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.
[0078] The wetting agent is a non-ionic wetting agent purchased from Evonik Degussa, model Tego Wet 270; the dispersing agent is acrylic BYK-163.
[0079] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly transparent invisible car cover self-cleaning film, and the specific steps include the following steps: S1: adding diluent, functional additive, silicone oil and basic emulsion into a high-speed mixer, and stirring at 1500rpm for 15min until uniform; S2: after adding nanoparticles, continue to maintain a speed of 1500rpm and stir for 20min; S3: finally add leveling agent, wetting agent and dispersant at a speed of 1000rpm, stir for 9min, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5h to obtain the product.
[0080] Example 2
[0081] Example 2 The first aspect provides a highly transparent invisible car cover self-cleaning film. The raw materials, in parts by mass, are: 30.5 parts of base emulsion, 35.6 parts of nanoparticles, 14.2 parts of functional additives, 24.8 parts of diluents, 21 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.
[0082] The base emulsion is a composition of modified acrylic emulsion and fluorocarbon emulsion, and the mass ratio of the two is 2.2:1.2.
[0083] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion with a viscosity of 240 mPa·s, a temperature of 25° C., and a solid content of 52.2 wt %. The product is a SH-1046 model product purchased from Hubei Longsheng Sihai New Materials Co., Ltd.
[0084] The fluorocarbon emulsion has a fluorine content of 11.6 wt % and a solid content of 46.5 wt %, and is purchased from Jining Tangyi Chemical Co., Ltd. under the model CF-801.
[0085] The nanoparticles are a composition of modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide, and the mass ratio of the three is 2.4:1.4:1.1.
[0086] The average particle size of nano-silicon dioxide is 55nm, and the average particle size of nano-zirconia is 14nm.
[0087] The preparation method of modified nano-alumina comprises the following steps, calculated by mass: S1: adding 3.6 parts of nano-alumina to a mixed solvent of ethanol and deionized water (a total of 180 parts of the mixed solvent, and a mass ratio of ethanol to deionized water of 1:4), uniformly dispersing by 220W ultrasonic dispersion, adjusting the pH to 9.8 with triethanolamine, then adding 0.82 parts of tetraethyl orthosilicate, 0.22 parts of isopropanol and 0.1 parts of silane coupling agent, heating to 68°C and keeping the temperature for reaction for 3 hours, after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated nano-alumina; S2: adding 4.2 parts of pretreated nano-alumina to 200 parts of deionized water, adding 0.3 8 parts of sodium dodecylbenzene sulfonate, 1.68 parts of succinic anhydride and 11.5 parts of hydrofluoric acid are kept at 65°C for 2h, and then 3.1 parts of aluminum nitrate trihydrate, 1.65 parts of terephthalic acid and 0.75 parts of isophthalic acid are added, mixed and stirred evenly, and transferred to a sealed reaction container; S3: Control the pressure of the sealed reaction container to 2.1MPa, heat the reaction at 200°C for 11.5h, and after the reaction is completed, naturally cool to 60°C to obtain a mixed solution, and then add 3.2 parts of zinc nitrate and 1.8 parts of dimethylimidazole to every 100 parts of the mixed solution, mix and stir, and keep warm for 2h. After completion, centrifuge and filter the product, wash it with ethanol for 3 times, and then vacuum dry it to obtain.
[0088] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0089] The average particle size of the modified nano-alumina is 691nm.
[0090] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.
[0091] The weight average molecular weight of polyethylene glycol methyl ether is 400 Da, and the product of the corresponding molecular weight model is purchased from Haian Petrochemical Company in Jiangsu Province.
[0092] The weight average molecular weight of the epoxy block polyether is 7800 Da, the ethylene oxide block content is 70 wt %, and the product is an ethylene oxide-propylene oxide block copolyether product of model L87 purchased from BASF.
[0093] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.
[0094] The HLB value of phenylethylphenol polyoxyethylene ether is 11, and it was purchased from the corresponding HLB value product sold by Nanjing Kexing Chemical Co., Ltd.; the HLB value of trimethylstyrenephenol polyoxyethylene ether is 16, and it was purchased from the corresponding HLB value product sold by Jiangsu Hai'an Petrochemical.
[0095] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.
[0096] The wetting agent is a non-ionic wetting agent purchased from Evonik Degussa, model Tego Wet 270; the dispersing agent is acrylic BYK-163.
[0097] The second aspect of the present embodiment provides a method for preparing the above-mentioned highly transparent invisible car cover self-cleaning film, and the specific steps include the following steps: S1: adding diluent, functional additive, silicone oil and basic emulsion into a high-speed mixer, and stirring at 1500rpm for 15min until uniform; S2: after adding nanoparticles, continue to maintain a speed of 1500rpm and stir for 20min; S3: finally add leveling agent, wetting agent and dispersant at a speed of 1000rpm, stir for 9min, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5h to obtain the product.
[0098] Comparative Example 1
[0099] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the high-transparency invisible car cover self-cleaning film, in parts by mass, are: 46.8 parts of base emulsion, 25.8 parts of nanoparticles, 15.5 parts of functional additives, 24.8 parts of diluents, 21 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.
[0100] Comparative Example 2
[0101] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the high-transparency invisible car cover self-cleaning film, in parts by mass, are: 40.6 parts of base emulsion, 39.5 parts of nanoparticles, 5.6 parts of functional additives, 24.8 parts of diluent, 21 parts of silicone oil, 2.2 parts of leveling agent, 3.8 parts of wetting agent, and 2.5 parts of dispersant.
[0102] Comparative Example 3
[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of the modified acrylic emulsion to the fluorocarbon emulsion is 4:0.6.
[0104] Comparative Example 4
[0105] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide is 0.5:2.5:2.2.
[0106] Comparative Example 5
[0107] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of modified nano-alumina comprises the following steps, measured in parts by mass: S1: adding 8.5 parts of nano-alumina to a mixed solvent of ethanol and deionized water (a total of 240 parts of the mixed solvent, and a mass ratio of ethanol to deionized water of 1:4), uniformly dispersing by 220W ultrasonic dispersion, adjusting the pH to 10 with triethanolamine, then adding 0.55 parts of tetraethyl orthosilicate, 0.14 parts of isopropanol and 0.04 parts of silane coupling agent, heating to 68°C and keeping the reaction for 3 hours, after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated nano-alumina; S2: adding 8.5 parts of pretreated nano-alumina to To 240 parts of deionized water, add 0.16 parts of sodium dodecylbenzene sulfonate, 1.1 parts of succinic anhydride and 5.5 parts of hydrofluoric acid, keep warm at 65°C for 2h, add 3.1 parts of aluminum nitrate trihydrate, 1.65 parts of terephthalic acid and 0.75 parts of isophthalic acid, mix and stir evenly, and transfer to a sealed reaction container; S3: control the pressure of the sealed reaction container to 2.1MPa, heat the reaction at 200°C for 11.5h, and after the reaction is completed, naturally cool to 60°C to obtain a mixed solution, then add 3.2 parts of zinc nitrate and 1.8 parts of dimethylimidazole to every 100 parts of the mixed solution, mix and stir, keep warm for 2h, after completion, centrifuge and filter the product, wash it with ethanol for 3 times, and then vacuum dry it to obtain.
[0108] Comparative Example 6
[0109] The specific implementation of this comparative example is basically the same as that of Example 1, except that the preparation method of modified nano-alumina comprises the following steps, measured in parts by mass: S1: adding 3.6 parts of nano-alumina to a mixed solvent of ethanol and deionized water (a total of 180 parts of the mixed solvent, with a mass ratio of ethanol to deionized water of 1:4), uniformly dispersing by 220W ultrasonic dispersion, adjusting the pH to 9.8 with triethanolamine, then adding 0.82 parts of tetraethyl orthosilicate, 0.22 parts of isopropanol and 0.1 parts of silane coupling agent, heating to 68°C and keeping the reaction for 3 hours, after the reaction is completed, centrifuging and filtering the product, washing with ethanol and drying to obtain pretreated nano-alumina; S2: adding 6.8 parts of pretreated nano-alumina to To 200 parts of deionized water, add 0.38 parts of sodium dodecylbenzene sulfonate, 1.68 parts of succinic anhydride and 11.5 parts of hydrofluoric acid, keep warm at 65°C for 2h, add 1.5 parts of aluminum nitrate trihydrate, 0.8 parts of terephthalic acid and 0.4 parts of isophthalic acid, mix and stir evenly, and transfer to a sealed reaction container; S3: control the pressure of the sealed reaction container to 2.1MPa, heat the reaction at 200°C for 11.5h, and after the reaction is completed, naturally cool to 60°C to obtain a mixed solution, then add 1.5 parts of zinc nitrate and 0.4 parts of dimethylimidazole to every 100 parts of the mixed solution, mix and stir, keep warm for 2h, after completion, centrifuge and filter the product, wash it with ethanol for 3 times, and then vacuum dry it to obtain.
[0110] Comparative Example 7
[0111] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 8:2:0.3.
[0112] Comparative Example 8
[0113] The specific implementation of this comparative example is basically the same as that of Example 1, except that the weight average molecular weight of the epoxy block polyether is 1600 Da, the ethylene oxide block content is 20 wt %, and the L42 ethylene oxide-propylene oxide block copolyether product is purchased from BASF.
[0114] Performance Evaluation
[0115] 1. Mechanical properties: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the self-cleaning films prepared in the examples and comparative examples, and tensile strength and elongation at break were tested using a universal tensile machine. The test values were the average values of 10 tests and recorded in Table 1.
[0116] 2. Self-cleaning performance: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the self-cleaning films prepared in the embodiments and comparative examples, and placed in an outdoor environment for 6 months in a fixed test group. The average environmental range was 26.8-28.2°C, and the average relative humidity range was 66.4-70.1%. After 6 months, the samples were taken back and naturally rinsed with clean water. The surface of the self-cleaning film sample was randomly cut to detect the percentage of dirt occupying the area. The test value was the average value of 10 tests and recorded in Table 1.
[0117] 3. Waterproof performance: For the self-cleaning membranes prepared in the embodiments and comparative examples, samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken, and the water contact angle on the membrane surface was tested by the sessile drop method. The test water droplet was 2.5 μL, and the test time was 15 s. The test value was the average of 10 tests and recorded in Table 1.
[0118] 4. Aging resistance: For the self-cleaning films prepared in the embodiments and comparative examples, samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken and placed in a constant temperature and humidity chamber at 68±3°C and a relative humidity of 75±2%. They were stored for 3 months and taken out after 3 months. The tensile strength of the film layer was tested before and after 3 months (tested by the performance test 1 method), and the retention rate of tensile strength was calculated. Retention rate % = (tensile strength of the film layer after 3 months / tensile strength of the film layer before 3 months) × 100%. The test values were taken as the average value of 10 tests and recorded in Table 1.
[0119] 5. Corrosion resistance: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the self-cleaning films prepared in the embodiments and comparative examples, and a salt spray corrosion resistance test was performed with 5 wt % NaCl. The samples were immersed in 5 wt % NaCl for 800 h. After the test, the samples were taken out to observe whether there were obvious film damage, tearing, corrosion oxidation, and curling. The tensile strength retention rate was tested again using the scheme in performance test 4. If there were no obvious above-mentioned phenomena and the tensile strength retention rate was ≥85%, it was considered qualified, otherwise it was considered unqualified. The qualified rate results of 50 samples in each group were recorded in Table 1.
[0120] Table 1 Performance test results
[0121]
[0122]
[0123] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 8 in terms of mechanical properties, self-cleaning properties, waterproof properties and aging corrosion resistance. This is mainly due to the combined effect of the functional additives, composite nanoparticles and other matching technical solutions specified in the present application. Comparative examples 1 to 8 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A highly transparent invisible car cover self-cleaning film, Features: The raw materials are as follows: 20-40 parts of base emulsion, 30-60 parts of nanoparticles, 10-20 parts of functional additives, 20-30 parts of diluents, 15-25 parts of silicone oils, 1-3 parts of leveling agents, 2-5 parts of wetting agents, and 1-3 parts of dispersants, in parts by mass. The base emulsion is a composition of modified acrylic emulsion and fluorocarbon emulsion; the mass ratio of the modified acrylic emulsion to the fluorocarbon emulsion is (2-3): (0.8-1.2); The modified acrylic emulsion is an organosiloxane-modified acrylic emulsion; The viscosity of the modified acrylic emulsion is 150 to 300 mPa·s at 25°C; The solid content of the modified acrylic emulsion is 50-55wt%; The fluorine content of the fluorocarbon emulsion is 10 to 15 wt %; The solid content of the fluorocarbon emulsion is 40-48wt%; The nanoparticles are a composition of modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide; The mass ratio of the modified nano-alumina, nano-silicon dioxide and nano-zirconium oxide is (2-2.5): (1-1.4): (1-1.4); Preparation method of modified nano alumina The following steps are involved: S1: Add nano-alumina to a mixed solvent of ethanol and deionized water, disperse evenly with 200-250W ultrasonic wave, adjust the pH to 9-10 with triethanolamine, then add tetraethyl orthosilicate, isopropanol and silane coupling agent, heat to 65-70°C and keep the reaction for 2.5-3h, after the reaction is completed, centrifuge and filter the product, wash with ethanol and dry it to obtain pretreated nano-alumina; S2: Add the pretreated nano-alumina to deionized water, add sodium dodecylbenzene sulfonate, succinic anhydride and hydrofluoric acid, keep the temperature at 60-80°C for 1.5-2h, add aluminum nitrate trihydrate, terephthalic acid and isophthalic acid, mix and stir evenly, and transfer to a sealed reaction container; S3: Control the pressure of the sealed reaction container to 2-2.1MPa, heat the reaction at 195-200°C for 10-12h, and naturally cool to 60-65°C after the reaction is completed to obtain a mixed solution, then add zinc nitrate and dimethylimidazole to every 100 parts of the mixed solution, mix and stir, keep the temperature for 1.5-2h, and after completion, centrifuge and filter the product, wash it with ethanol for 2-3 times, and then vacuum dry it to obtain; The mass ratio of the nano-alumina, tetraethyl orthosilicate, isopropyl alcohol and silane coupling agent is (3.5-3.8): (0.8-0.9): (0.2-0.25): (0.08-0.12); The mass ratio of the pretreated nano-alumina, sodium dodecylbenzene sulfonate, succinic anhydride and hydrofluoric acid is (4-4.5): (0.3-0.4): (1.5-1.8): (10-12); The average particle size of the modified nano-alumina is 640-780 nm; The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and arylphenol polyoxyethylene ether; The mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).
2. The highly transparent invisible car cover self-cleaning film according to claim 1, Features: The mass ratio of the basic emulsion, the nanoparticles and the functional additive is (30-38): (35-45): (12-18).
3. The highly transparent invisible car cover self-cleaning film according to claim 2, Features: The mass ratio of the base emulsion, the diluent and the silicone oil is (30-38): (22-26): (18-24).
4. The highly transparent invisible car cover self-cleaning film according to claim 3, Features: The average particle size of the nano silicon dioxide is 40 to 60 nm.
5. The highly transparent invisible car cover self-cleaning film according to claim 4, Features: The average particle size of the nano zirconium oxide is 10-20 nm.
6. The highly transparent invisible car cover self-cleaning film according to claim 5, Features: The average particle size of the nano-alumina is 15-25 nm.
7. The highly transparent invisible car cover self-cleaning film according to claim 6, Features: The weight average molecular weight of the polyethylene glycol methyl ether is 400-800 Da.
8. The highly transparent invisible car cover self-cleaning film according to claim 7, Features: The weight average molecular weight of the epoxy block polyether is 6000-8000 Da.
9. A method for preparing the highly transparent invisible car cover self-cleaning film according to any one of claims 1 to 8, Features: The specific steps include the following: S1: Add diluent, functional additive, silicone oil and basic emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours.
10. Use of the highly transparent invisible car cover self-cleaning film according to any one of claims 1 to 8 in the field of protective films for automobile bodies, train bodies, automobile windows and train windows.
Citation Information
Patent Citations
Super-wear-resistant self-cleaning coating and preparing method thereof
CN109627963A
Environment-friendly heat insulation paint and preparation method thereof
CN109897521A
paint
US20090005484A1
Cited By
Bending-resistant transparent sheath for coating invisible optical cable and preparation method of bending-resistant transparent sheath
CN120554826A
